What will it cost to prevent violence against women and girls in low- and middle-income countries? Evidence from Ghana, Kenya, Pakistan, Rwanda, South Africa and Zambia. Issue 7 (18th June 2020) - Torres-Rueda, Sergio; Ferrari, Giulia; Orangi, Stacey; Hitimana, Regis; Daviaud, Emmanuelle; Tawiah, Theresa; Prah, Rebecca Kyerewaa Dwommoh; Karmaliani, Rozina; Kapapa, Eleonah; Barasa, Edwine; Jewkes, Rachel; Vassall, Anna
Abstract: Violence against women and girls (VAWG) is a global problem with profound consequences. Although there is a growing body of evidence on the effectiveness of VAWG prevention interventions, economic data are scarce. We carried out a cross-country study to examine the costs of VAWG prevention interventions in low- and middle-income countries. We collected primary cost data on six different pilot VAWG prevention interventions in six countries: Ghana, Kenya, Pakistan, Rwanda, South Africa and Zambia. The interventions varied in their delivery platforms, target populations, settings and theories of change. We adopted a micro-costing methodology. We calculated total costs and a number of unit costs common across interventions (e.g. cost per beneficiary reached). We used the pilot-level cost data to model the expected total costs and unit costs of five interventions scaled up to the national level. Total costs of the pilots varied between ∼US 208 000 in a small group intervention in South Africa to US 2 788 000 in a couples and community-based intervention in Rwanda. Staff costs were the largest cost input across all interventions; consequently, total costs were sensitive to staff time use and salaries. The cost per beneficiary reached in the pilots ranged from ∼US 4 in a community-based intervention in Ghana to US 1324 for one-to-one counselling in Zambia. When scaled up to the national level, total costs ranged from US 32 million in Ghana to US 168 million in Pakistan. Cost per beneficiary reached at scale decreased for all interventions compared to the pilots, except for school-based interventions due to differences in student density per school between the pilot and the national average. The costs of delivering VAWG prevention vary greatly due to differences in the geographical reach, number of intervention components and the complexity of adapting the intervention to the country. Cost-effectiveness analyses are necessary to determine the value for money of interventions.